VD_FINDINFO Jug / 2025 / 314 vom 5. Februar 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, VOIES DE FAIT, POSITION DE GARANT, VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION | 126 al. 2 CP, 219 CP, 10 CPP (CH), 9 CPP (CH)